Size effect in transient thermal fatigue testing and thermo-mechanical screening of coatings. (17th June 2008) - Dour, G.; Medjedoub, F.; Diaconu, G.; Girardin, D.; Michrafy, A.; Loulou, T.M.; Rezai-Aria, F.
In an attempt to bring new ideas to thermal fatigue analysis of tools, we propose the principle of the two driving forces leading to damage by Thermal Fatigue (TF). After a definition of the two driving forces based on temperature and thermo-mechanical loadings, a procedure for evaluating them for in-service tools is proposed. In order to compare thermo-mechanical loadings in industrial tools to laboratory specimen, a normalisation of the thermo-mechanical equations is proposed. A size effect in those thermal mechanical problems is justified and used to set an original rule to design transient TF tests. In a second example related to coating tools or bi-materials tools, the concept of thermo-mechanical screening is explained: it corresponds to the optimum combination of materials properties leading to the vanishment of thermal stresses at the mating surface of a tool. An example is given that shows some conditions in which this can happen, depending on the combination of material properties. An example of application is then proposed.